2015
DOI: 10.1002/2014gc005429
|View full text |Cite
|
Sign up to set email alerts
|

Split-beam echo sounder observations of natural methane seep variability in the northern Gulf of Mexico

Abstract: A method for positioning and characterizing plumes of bubbles from marine gas seeps using an 18 kHz scientific split-beam echo sounder (SBES) was developed and applied to acoustic observations of plumes of presumed methane gas bubbles originating at approximately 1400 m depth in the northern Gulf of Mexico. A total of 161 plume observations from 27 repeat surveys were grouped by proximity into 35 clusters of gas vent positions on the seafloor. Profiles of acoustic target strength per vertical meter of plume he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…There is a high degree of variability in volumetric gas flow rates, both between investigators and the different methods used in each individual study, and for sites visited multiple times (e.g., Clark et al, , visited La Goleta in 2002, 2003, and 2005). This variability is consistent with other studies for which seep activity has been observed to vary over timescales of seconds to minutes and hours to years (Boles et al, ; Clark et al, ; Clark et al, ; Hornafius et al, ; Jerram et al, ; Kinnaman et al, ; Leifer & Boles, ; Quigley et al, ). Quigley et al () reported a decrease of seep activity of 80% in the vicinity of Platform Holly in a 22‐year period, by comparing the area of detected seeps (but not volumetric gas flow rates) to those of Fischer and Stevenson (), and that reduction has been hypothesized to be linked to petroleum extraction from Platform Holly.…”
Section: Comparison Of Volumetric Gas Flux Observations To Previous Esupporting
confidence: 91%
“…There is a high degree of variability in volumetric gas flow rates, both between investigators and the different methods used in each individual study, and for sites visited multiple times (e.g., Clark et al, , visited La Goleta in 2002, 2003, and 2005). This variability is consistent with other studies for which seep activity has been observed to vary over timescales of seconds to minutes and hours to years (Boles et al, ; Clark et al, ; Clark et al, ; Hornafius et al, ; Jerram et al, ; Kinnaman et al, ; Leifer & Boles, ; Quigley et al, ). Quigley et al () reported a decrease of seep activity of 80% in the vicinity of Platform Holly in a 22‐year period, by comparing the area of detected seeps (but not volumetric gas flow rates) to those of Fischer and Stevenson (), and that reduction has been hypothesized to be linked to petroleum extraction from Platform Holly.…”
Section: Comparison Of Volumetric Gas Flux Observations To Previous Esupporting
confidence: 91%
“…In the gas hydrate stability pressure and temperature field maintaining a hydrate shell requires a minimum dissolved concentration of gas in the water (Chen et al 2013), suggesting that hydrate-shelled bubbles may ascend as part of a multiphase plume. The shell encapsulates, and effectively armors, the bubble from dissolution until it reaches the top gas hydrate stability (TGHS) where the NGH quickly dissociates and dissolves (Rehder et al 2002, Levine 2015, Warzinski et al 2014, Jerram, Weber, and Beaudoin 2015. The shell encapsulates, and effectively armors, the bubble from dissolution until it reaches the top gas hydrate stability (TGHS) where the NGH quickly dissociates and dissolves (Rehder et al 2002, Levine 2015, Warzinski et al 2014, Jerram, Weber, and Beaudoin 2015.…”
Section: Effect Of Ascending Gas Bubbles On Acoustic Reflection Withimentioning
confidence: 99%
“…Characterizing emissions is improving our understanding of the transport processes and allowing estimates and quantification of fluxes (Wilson, Leifer, and Maillard 2015, Leifer and Judd 2015, Leifer 2015, von Deimling et al 2015, Vielstädte et al 2015, Weber et al 2014, Wiggins et al 2015, Nauw, Linke, and Leifer 2015, Jerram, Weber, and Beaudoin 2015, Frouzova, Tušer, and Stanovsky 2015 that will provide more detail to the CH 4 budgets involved. Furthermore, following the Deep Water Horizon disaster in the Gulf of Mexico detailed mapping of the region near the wellhead revealed multiple sources of natural hydrocarbons (Smith et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Not long after the first military applications, acoustic water column mapping with echo sounders was applied to fisheries science, for which the detection and quantification of fish distributions were the primary focus (Kimura, 1929;MacLennan, 1990). The applications of acoustic water column mapping have broadened in recent years to include marine ecosystem acoustics (Benoit-Bird and Lawson, 2016;Godø et al, 2014), observations of gas bubbles and oil droplets associated with natural seeps (Jerram et al, 2015;Merewether et al, 1985), and fossil fuel production (Hickman et al, 2012;. Acoustic imaging of the water column has also been used within the field of physical oceanography; single-beam echo sounders can capture fine-scale oceanographic structures typically attributed to biological scattering or turbulent microstructures (Klymak and Moum, 2003;Pingree and Mardell, 1985;Trevorrow, 1998).…”
Section: Introductionmentioning
confidence: 99%